Teachers’ and Language Learners’ Perceptions and Challenges of the Panrita English Village: A Lesson from English Global Maritime - Limbong, Sunarlia; Susanto, Rudy; Sulistiana, Oktavera; Rohman, Moh. Aziz; Idris, Zainal Yahya (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
The study aims to investigate how cadets and teachers perceive and explore the main challenges faced in joining the Panrita English Village program. This study used a qualitative approach to gain an in-depth understanding of cadets’ and teachers’ perceptions and the main challenges of the program, with nine cadets and three lecturers. The techniques of data analysis used semi-structured interviews, participant observation, and document analysis. Findings show that most cadets and teachers loved the program since it was not monotonous, gave good chances for every participant to speak, and used a small class structure with one teacher handling just 10–12 cadets. Thoughts to boost confidence in English included role-playing, group debates, and language games. The interview results reveal significant challenges faced by cadets participating program. These challenges typically arise from scheduling conflicts caused by academic commitments, mandatory university activities, and unplanned extracurricular engagements. The responses provide insight into how these constraints influence participation and suggest potential improvements to enhance engagement and learning outcomes. This concludes that the program has successfully improved cadets' English speaking skills through interactive activities such as role-playing, debates, and language games, but its sustainability and broader impact depend on addressing scheduling constraints and implementing more flexible learning. The implication needs to be developed with a more flexible learning approach so that its success in improving cadets' English-speaking skills can be sustained despite facing academic schedule constraints. Further research needs to involve more institutions and longitudinal designs to strengthen the program's impact and sustainability.